Adenylate cyclase toxin from Bordetella pertussis synergises with lipopolysaccharide to promote innate IL-10 production and enhance the induction of Th2 and regulatory T cells - LAVELLE, EDWARD; MILLS, KINGSTON (American Society for Microbiology, 2004)
Adenylate cyclase toxin (CyaA) from Bordetella pertussis can subvert host immune responses allowing bacterial colonization. Here we have examined its adjuvant and immunomodulatory properties and the possible contribution of lipopolysaccharide (LPS), known to be present in purified CyaA preparations. CyaA enhanced antigen-specific interleukin-5 (IL-5) and IL-10 production and immunoglobulin G1 antibodies to coadministered antigen in vivo. Antigen-specific CD4+-T-cell clones generated from mice immunized with antigen and CyaA had cytokine profiles characteristic of Th2 or type 1 regulatory T (Tr1) cells. Since innate immune cells direct the induction of T-cell subtypes, we examined the influence of CyaA on activation of dendritic cells (DC) and macrophages. CyaA significantly augmented LPS-induced IL-6 and IL-10 and inhibited LPS-driven tumor necrosis factor alpha and IL-12p70 production from bone marrow-derived DC and macrophages. CyaA also enhanced cell surface expression of CD80, CD86, and major histocompatibility class II on immature DC. The stimulatory activity of our CyaA preparation for IL-10 production and CD80, CD86, and major histocompatibility complex class II expression was attenuated following the addition of polymyxin B or with the use of DC from Toll-like receptor (TLR) 4-defective mice. However, treatment of DC with LPS alone at the concentration present in the CyaA preparation (0.2 ng/ml) failed to activate DC in vitro. Our findings demonstrate that activation of innate cells in vitro by CyaA is dependent on a second signal through a TLR and that CyaA can promote Th2/Tr1-cell responses by inhibiting IL-12 and promoting IL-10 production by DC and macrophages.
PUBLISHED
Keywords: Biochemistry